2010
DOI: 10.21608/jva.2010.44900
|View full text |Cite
|
Sign up to set email alerts
|

Gross Anatomical, Histological and Histochemical Studies of the Esophagus of the African Giant Rat (AGR) (Cricetomys gambianus-Waterhouse, 1840)

Abstract: Forty African Giant Rats (AGRs) were used for the present studies. The mean weight and length of the esophagus were 1.39 g (± 0.08) and 11.78 cm (± 0.53) respectively. These values accounted for 0.13 % and 5.5 % of the weight and length of the gastrointestinal tract, respecttively. Grossly the esophagus was observed to lie dorsal to the trachea throughout its length. The epithelial lining of the esophagus was observed to be made up of nonkeratinized stratified squamous cells. The lamina muscularis and mucous g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 7 publications
8
9
1
Order By: Relevance
“…The pancreas observed between these limbs . The U-shape of duodenum in the current animals was commonly observed in the other(this result disagreement with other studies such as Agur et al (14) those said the duodenum it was found to form an "S" shaped curve and also the (15,16) mention the duodenum it found is a C-shaped or horseshoe-shaped structure.…”
Section: Resultscontrasting
confidence: 91%
“…The pancreas observed between these limbs . The U-shape of duodenum in the current animals was commonly observed in the other(this result disagreement with other studies such as Agur et al (14) those said the duodenum it was found to form an "S" shaped curve and also the (15,16) mention the duodenum it found is a C-shaped or horseshoe-shaped structure.…”
Section: Resultscontrasting
confidence: 91%
“…These are in conformity with the findings of Weaver and Carrick (1989), who observed changes in upper intestinal epithelial morphology and kinetics in the growing guinea pig. Findings from the study, especially with the adult African giant rat conform with those of Nzalak et al (2015) who investigated the gross and histological features of small intestine of the adult African giant rat. As observed with the adult rats in the present study, Nzalak et al (2015), had earlier reported that the jejunum is the longest portion of the small intestine of the African giant rat while the ileum is the shortest.…”
Section: Discussionsupporting
confidence: 75%
“…Findings from the study, especially with the adult African giant rat conform with those of Nzalak et al (2015) who investigated the gross and histological features of small intestine of the adult African giant rat. As observed with the adult rats in the present study, Nzalak et al (2015), had earlier reported that the jejunum is the longest portion of the small intestine of the African giant rat while the ileum is the shortest. It could be inferred that the digestive and absorptive roles of the small intestine in this rat is carried out more at the jejunum.…”
Section: Discussionsupporting
confidence: 75%
“…The African giant rat (AGR) is found in abundance in the rainforests, grasslands and human habitations of Central and West Africa (Ali et al, 2011; Nzalak et al., 2015). The rat is social living in burrows, around drains and houses and is seen frequently at night.…”
Section: Introductionmentioning
confidence: 99%
“…The rat is social living in burrows, around drains and houses and is seen frequently at night. The animal walks and runs on the four legs and is a good climber and jumper (Nzalak et al., 2015).…”
Section: Introductionmentioning
confidence: 99%